Determinan Kesehatan Mental Anak Yatim Dan Piatu Di Lembaga Kesejahteraan Sosial Anak Kabupaten Bireuen - Raudhati, Sri (Universitas Wiralodra, 2020)
WHO said that mental health disorders are more prone to attack the millennial generation, and mental health disorders are most vulnerable to orphaned adolescents living in orphanages, because they have lost love and direct attention from their biological fathers and mothers. The purpose of this study was to determine the factors related to the mental health of orphans, orphans and orphans in the Bireuen District Child Welfare Institution. Research Methodology:This research is a quantitative study, using a cross sectional study design. Sampling using purposive sampling technique, with a sample size of 104 children. The statistical test used in the data analysis was the logistic regression test using the stata program 15. Results: It was found that 25% of children experienced behavioral and emotional difficulties, where the largest proportion was peer problems 31.7%, then emotional symptoms 27.9%, behavioral problems 19.2 %, and hyperactivity 7.7%, while the problem of decreasing children's prosocial behavior was 14.4%. The results of the multivariate logistic test showed that female gender, other reasons, the child's age at the death of their parents â‰¤5 years, and families who rarely visited had a significant relationship with behavioral and emotional difficulties (P=0.004; P=0.012; P=0.007 ; P=0.003 respectively), While the factors that had a significant relationship with prosocial behavior were other reasons for entering the orphanage, the status of the orphaned children, the health condition of the sick children, and the children who experienced conflicts (P=0.031; P=0.010, P=0.011; P=0.002 respectively). Suggestion: With the results of this study, it is expected for orphanage leaders and caregivers to further optimize the services of counseling and social support programs so that they are able to find solutions to children's mental emotional problems.